2018
DOI: 10.1016/j.bpj.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Potential Distinctly Modulates Mobility and Signaling of IL-2 and IL-15 Receptors in T Cells

Abstract: The high electric field across the plasma membrane might influence the conformation and behavior of transmembrane proteins that have uneven charge distributions in or near their transmembrane regions. Membrane depolarization of T cells occurs in the tumor microenvironment and in inflamed tissues because of K release from necrotic cells and hypoxia affecting the expression of K channels. However, little attention has been given to the effect of membrane potential (MP) changes on membrane receptor function. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Our analysis demonstrated that γ c -chains had a fast and a slow diffusing subpopulation, but the dimeric/oligomeric form belonged fully to the slow species. The diffusion coefficient of this complex (∼0.1 μm 2 /s) was similar to that measured in the plasma membrane for IL-2Rα and IL-15Rα subunits (37,57), suggesting diffusion in an intracellular membrane. The diffusion coefficient of the fast fraction of the monomeric γ c was 2 orders of magnitude higher, similar to that of the soluble controls: EGFP, mCherry, and the EGFP-mCherry fusion (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Our analysis demonstrated that γ c -chains had a fast and a slow diffusing subpopulation, but the dimeric/oligomeric form belonged fully to the slow species. The diffusion coefficient of this complex (∼0.1 μm 2 /s) was similar to that measured in the plasma membrane for IL-2Rα and IL-15Rα subunits (37,57), suggesting diffusion in an intracellular membrane. The diffusion coefficient of the fast fraction of the monomeric γ c was 2 orders of magnitude higher, similar to that of the soluble controls: EGFP, mCherry, and the EGFP-mCherry fusion (Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Overall, this scheme strongly resembles what is quite well established concerning the functional roles for IK Ca in defined cell types in the immune system [ 42 , 43 ]. These insights are the basis for ongoing, active searches for IK Ca targeted approaches to alter immune function [ 44 ] based in part on alterations of [Ca 2+ ] i signaling in lymphocytes and T-cells [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Membrane depolarization could also lead to enhanced IL-2 signaling in T reg s and, consequently, to suppressed antitumor immune surveillance by such an unbalanced ionic environment ( Nagy et al, 2018 ). The high [K + ]-adapted tumor-infiltrating lymphocytes are less functional than the normal ones.…”
Section: Therapeutical Approaches and Ion Channels In Pdacmentioning
confidence: 99%